2021
DOI: 10.1007/s10646-021-02378-6
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine disrupting potency and toxicity of novel sophorolipid quaternary ammonium salts

Abstract: A new class of biosurfactants, namely quaternary ammonium sophorolipids (SQAS), suitable for pharmaceutical applications, was tested for the evaluation of their (anti)estrogenic and (anti)androgenic potency with the help of YES/YAS assays. Also their toxicity towards yeasts (Saccharomyces cerevisiae) and bacteria (Escherichia coli) was checked. The results achieved for SQAS, which can be regarded as potential micropollutants, were compared with those obtained for two well-known micropollutants diclofenac and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…It was reported that QACs signi cantly decreased reproduction, caused birth defects and impacted the development of ovaries in mice and rats (Jiao et al 2017, Hrubec et al 2021, Matsumoto et al 2021). In the yeast assays and in vitro cell line studies, QACs impacted hormones that are important in reproduction (Hrubec et al 2021, Liwarska-Bizukojc et al 2021. Notably, the reproduction process connects adjacent generations and its changes by pollutants can represent intergenerational in uences.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that QACs signi cantly decreased reproduction, caused birth defects and impacted the development of ovaries in mice and rats (Jiao et al 2017, Hrubec et al 2021, Matsumoto et al 2021). In the yeast assays and in vitro cell line studies, QACs impacted hormones that are important in reproduction (Hrubec et al 2021, Liwarska-Bizukojc et al 2021. Notably, the reproduction process connects adjacent generations and its changes by pollutants can represent intergenerational in uences.…”
Section: Introductionmentioning
confidence: 99%